The Litani River, Lebanon: An Assessment and Current Challenges (Water Science and Technology Library,, 2018)
This book presents a collection of chapters covering research on the Litani River Basin. The Litani River Basin occupies about a quarter of Lebanon's surface area, and it has recently been subject to severe conditions such as contamination and decreased discharge. This motivated the Lebanese government to take action and start working on the remediation of the river. These actions are also supported by international organizations including the World Bank.